To the knowledge of the subtribe Pericalina Hope, 1838 (Coleoptera, Carabidae, Lebiinae), with description of new genus, new subgenus and species from Oriental region - Anichtchenko, Alexander (Zootaxa, 2024)
A new genus Acoptodera gen. n. is described to place Coptodera piligera Chaudoir, 1883 previously attributed to genus Trichocoptodera Louwerens, 1958, as well as new subgenus Pericalocephala subgen. n. to place remarkable new species from Vietnam: Acoptodera (Pericalocephala) paradoxa sp. n. By the presence of hairs on head, pronotum and elytra, new genus is similar with Trichocoptodera Louwerens, 1958, but can be easely distinguished by flattened pronotum with wide lateral margins and by rounded elytra with serrate edges and fringe of setae on the sides. The status and characters of genera thought to be near relatives of Coptodera genus-group, are briefly discussed. Images of habitus and genitalia are provided.